2023
DOI: 10.5194/egusphere-2023-706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oceanographic Processes Favoring Deoxygenation Inside Patagonian Fjords

Abstract: Abstract. The dissolved oxygen (DO) levels of oceanic-coastal waters has decreased over the last decade owing to the increase in surface water temperature caused by climate change. In addition, biological and human activity in coastal zones, bays, and estuaries has contributed to the acceleration of current deoxygenation. The Patagonian fjord and channel system is one world region where low DO water (LDOW, 30 %–60 % oxygen saturation) and hypoxia conditions (< 30 % oxygen saturation, 2 ml L−1 or 89.2 µmol L… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In this sense, it is important to clarify that salmon was a non-indigenous species in Chile when the farms started in the area, and, therefore, the possible effects derived from salmon cultivation can be considered an anthropogenic effect, as it is eutrophication. Although some areas are at higher risk of eutrophication than others, e.g., due to high aquaculture loads [ 85 ], a recent study showed that the Patagonian fjords have not undergone significant changes in the nutrient concentrations of their water columns in the last 50 years [ 86 ], consistent with some features of system 2. Finally, it has been recently recognized that the seasonal upwelling processes on the adjacent oceanic shelf [ 87 , 88 ] give the fjord system conditions consistent with those of system 1.…”
Section: Learning To Live With Hab: Some Lessonsmentioning
confidence: 87%
“…In this sense, it is important to clarify that salmon was a non-indigenous species in Chile when the farms started in the area, and, therefore, the possible effects derived from salmon cultivation can be considered an anthropogenic effect, as it is eutrophication. Although some areas are at higher risk of eutrophication than others, e.g., due to high aquaculture loads [ 85 ], a recent study showed that the Patagonian fjords have not undergone significant changes in the nutrient concentrations of their water columns in the last 50 years [ 86 ], consistent with some features of system 2. Finally, it has been recently recognized that the seasonal upwelling processes on the adjacent oceanic shelf [ 87 , 88 ] give the fjord system conditions consistent with those of system 1.…”
Section: Learning To Live With Hab: Some Lessonsmentioning
confidence: 87%
“…World Ocean Atlas data are available at https://odv.awi.de/ and https://www.ncei.noaa.gov/products/world-ocean-atlas. In situ hydrographic profiles and time series collected along the Patagonian fjords are available at the Zenodo (Linford et al., 2023a; https://doi.org/10.5281/zenodo.7799354, and Linford et al., 2023b; https://doi.org/10.5281/zenodo.7799378).…”
Section: Data Availability Statementmentioning
confidence: 99%